(untitled) (Journal of the College of Basic Education, 2026)
(The concept of human civilization, its foundations, pillars, and ways to advance it from the perspective of the Holy Qur’an). This research aims to demonstrate that the Holy Qur’an is the most important source of knowledge known to the history of humanity, as this precious book speaks about the various aspects of knowledge, whether economic, social, political, or other. Among the aspects of knowledge that received the attention of the Holy Qur’an is the civilizational aspect of nations and peoples, and you find this clear through its talk about divine laws, and about past nations, as it contained verses that spoke about those laws, and their impact on the course of nations, societies and individuals, and reinforced that with some examples of nations that practiced those laws, which affected them either negatively or positively, as in the civilization of Aad, Thamud, the Pharaonic civilization, or the Sabaean civilization. The Holy Quran spoke about the factors that led to the prosperity, continuity and survival of civilizations in many of its verses, and the person who researches the Book of God can stand on those factors in detail. The most dangerous thing that can befall a nation is the loss of its cultural identity, for cultural identity is the most valuable asset any society possesses.